Use of intravenous lipid therapy in a cat with carprofen overdose. Issue 4 (29th February 2020) - Chumbler, Nathan S.; Schildt, Julie C.; Mawby, Diane I.; Papich, Mark G.
Abstract: Intravenous lipid emulsion (ILE) was administered to a cat with no adverse effects. This case report postulates that ILE can be used for the treatment of carprofen toxicity in cats and supports the lipid sink theory as the main mechanism of action. Abstract : Intravenous lipid emulsion (ILE) was administered to a cat with no adverse effects. This case report postulates that ILE can be used for the treatment of carprofen toxicity in cats and supports the lipid sink theory as the main mechanism of action.